2010
DOI: 10.1159/000320520
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Colorectal Cancer with and without Bevacizumab: A Phase III Study

Abstract: Objective: The objective of this phase III trial was to compare chemotherapy combined with bevacizumab versus chemotherapy alone in the treatment of patients with advanced colorectal cancer. Methods: From September 2004 till September 2008, 222 treatment-naive patients were enrolled and divided into 2 arms: 114 arm A patients were treated with leucovorin, 5-fluorouracil plus irinotecan in combination with bevacizumab, and 108 arm B patients were treated as above without bevacizumab. All patients were stage IV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 49 publications
5
75
1
3
Order By: Relevance
“…Two trials 22,23 underwent FLU + LEU based chemotherapy, with 349 patients involved; 3 trials 10,25-29 underwent IFL-based chemotherapy, with 1,249 patients involved; 3 trials 15,[30][31][32] underwent FOLFOX based chemotherapy, with 3,834 patients involved; 1 trial underwent CAP based 33,34 chemotherapy, with 313 patients involved; 1 trial 35 underwent both CAP + OXA based and FOLFOX based chemotherapy, with 700 patients involved, respectively. Seven trials 10,15,[22][23][24][25][26][27][30][31][32] were completed in USA, the other three trials were completed in Greece, 28 China 29 and Australia, 33,34 respectively. In meta-analyses done for OS and PFS when comparing targeted agent-BEV added to CTX versus CTX alone in the treatment of CRC, BEV is associated with evidently decreased HR [ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two trials 22,23 underwent FLU + LEU based chemotherapy, with 349 patients involved; 3 trials 10,25-29 underwent IFL-based chemotherapy, with 1,249 patients involved; 3 trials 15,[30][31][32] underwent FOLFOX based chemotherapy, with 3,834 patients involved; 1 trial underwent CAP based 33,34 chemotherapy, with 313 patients involved; 1 trial 35 underwent both CAP + OXA based and FOLFOX based chemotherapy, with 700 patients involved, respectively. Seven trials 10,15,[22][23][24][25][26][27][30][31][32] were completed in USA, the other three trials were completed in Greece, 28 China 29 and Australia, 33,34 respectively. In meta-analyses done for OS and PFS when comparing targeted agent-BEV added to CTX versus CTX alone in the treatment of CRC, BEV is associated with evidently decreased HR [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analyses were done basing on different CTX, significantly decreased HRs for subtotal effects in OS were identified in the regimens about FLU + LEU based and FOLFOX based chemotherapies with/without BEV, with no evidence of statistical heterogeneity; while no significant differences were identified between CAP based chemotherapy with/ without BEV (with no heterogeneity was identified) and IFL based chemotherapy with/without BEV, but with evidence of statistical heterogeneity (I 2 = 80.1%, p = 0.007) in IFL group. Sensitivity analyses were performed, and statistical heterogeneity disappeared after eliminating trial 4, 28 which led to funnel-plot asymmetry. Additionally, subgroup analyses for PFS were done basing on similar CTX, with evident decreased HRs for all of the subgroups; but significant heterogeneity was found in FOLFOX group (I 2 = 81.9%, q = 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of bevacizumab to XELOX resulted in PFS ranging between 9.3-11.4 mo, OS ranging between 20.3-27.4 mo and a RR ranging between 46%-67.5% (Hochster et al, 2008;Tol et al, 2009;Doi et al, 2010;Cassidy et al, 2011;Uchima et al, 2014). Previous studies reported that the median PFS was between 9-12 months and the median OS was between 22-31.3 months and RR was 57.9% with FOLFIRI-Bev (Fuchs et al, 2007;Hecht et al, 2009;Sobrero et al, 2009;Stathopoulos et al, 2010;Ducreux et al, 2013;Becouarn et al, 2014). In our study, the median PFS was 9.6 months in Group 1 and 9 months in Group 2 (p=0.019).…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, investigators reported various partial response rates such as 47.5 (Becouarn et al, 2014), 40.1% (Pectasides et al, 2012) and 36.8% (Stathopoulos et al, 2010) with FOLFIRI-Bev. Lopez et al, reported a 8.4% complete response, 42.1% partial response, 16.8% stable disease and 32.6% progressive disease with FOLFIRI-Bev (Lopez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%